MODERN PEDAGOGICAL TECHNOLOGIES FOR PRESERVING AND STRENGTHENING STUDENTS’ HEALTH IN SCHOOL EDUCATION - Jumayeva Marjona Namoz qizi (International Journal of Literature and Language Studies, 2026)
The preservation and strengthening of students’ health has become one of the strategic priorities of modern school education. Contemporary educational practice increasingly recognizes that academic achievement cannot be separated from physical, psychological, social and emotional well-being. In this regard, schools are not only institutions for transmitting knowledge, but also important social environments where healthy lifestyles, hygienic culture, emotional stability, self-regulation, physical activity and responsible attitudes toward health are formed. This article examines modern pedagogical technologies aimed at preserving and strengthening students’ health in school education. Special attention is paid to health-preserving technologies, interactive and activity-based learning, digital health education tools, physical activity integration, socio-emotional learning, project-based approaches, inclusive health-oriented education and cooperation among teachers, parents and the wider community.